Energy-dependent timescales in the dissociation of diiodothiophene dication - Kukk Edwin; Pihlava Lassi; Kooser Kuno; Stråhlman Christian; Maclot Sylvain; Kivimäki Antti (ROYAL SOC CHEMISTRY, 2025)
Photodissociation molecular dynamics of gas-phase 2,5-diiodothiophene molecules was studied in an electron-energy-resolved electron-multi-ion coincidence experiment performed at the FinEstBeAMS beamline of MAX IV synchrotron. Following the photoionization of the iodine 4d subshell and the Auger decay, the dissociation landscape of the molecular dication was investigated as a function of the Auger electron energy. Concentrating on an major dissociation pathway, C4H2I2S2+ -> C4H2S+ + I+ + I, and accessing the timescales of the process via ion momentum correlation analysis, it was revealed how this three-body process changes depending on the available internal energy. Using a generalized secondary dissociation model, the process was shown to evolve from secondary dissociation regime towards concerted dissociation as the available energy increased, with the secondary dissociation time constant changing from 1.5 ps to 129 fs. The experimental results were compared with simulations using a stochastic charge-hopping molecular mechanics model. It represented the observed trend and also gave a fair quantitative agreement with the experiment.